Miasto podzielone, miasto uwikłane. Literackie portrety Jerozolimy w twórczości izraelskiego poety Jehudy Amichaja - Piątek, Anna (Studia Azjatystyczne, 2016)
Yehuda Amichai (1924-2000), one of the greatest contemporary Israeli poets, lived and worked in Jerusalem for decades. In his works, he presents the image of Jerusalem as a city with a long and complicated history, a matter of dispute and a unique place on the map of the world. With remarkable skill he paints portraits of the holy city of three religions, an important center for many cultures, and a place of residence of several communities. From each of these perspectives (religious, political and social), Jerusalem in Amichai’s texts appears as a diversified city entangled in antagonisms. This article is intended to present selected fragments of the poet’s texts describing these urban confrontations from the perspective of an individual – a sensitive and a concerned resident of Jerusalem. Then texts quoted show that Amichai sees his city as a microcosm in which mutual relations and tensions lose their merely local significance and gain a universal human meaning. Scenes from everyday life become symbolic and acquire universal sense. History, an integral part of the Jerusalem landscape, involves the residents and affects their perception of the world.